New heritages, a new Brazil? An analysis of federal heritage policies after the 1980s - Marins, Paulo César Garcez (2016)
The article examines the practices of conservation of the cultural heritage adopted by the federal government since the democratization of the country in the 1980s, focusing on the heritages nominated by the “tombamento” and “registro”. It analyzes to what extent national identity concepts traditionally welcomed by IPHAN since the Vargas dictatorship have been effectively revised when new protected heritages are selected.